Promising Research and Development Results in the Field of Image and Speech Signal Processing - D. S. Likhachov; J. Ma; N. A. Petrovsky; I. S. Azarov; V. Yu. Tsviatkou (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An analysis of the prospects for the development of technologies for processing images and speech signals is presented. The main results in these areas obtained in recent years in the relevant scientiﬁc schools of Belarusian State University of Informatics and Radioelectronics are presented. It is shown that the use of machine learning technologies in combination with methods of digital processing of images and speech signals can signiﬁcantly increase the eﬃciency of systems for their recognition and classiﬁcation.